Foreign Investment in The Era of Globalization: A Review of Legal Protection in The Perspective of National and International Law - Layla Qodri Ani; Amanda Khoirun Nisa; Amanda Gheanisa Lutfi; Falah Al Ghozali (Universitas Muhammadiyah Surakarta, 2024)
Introduction: This paper presents an overview of the legal protection of foreign investment in the context of globalization. It aims to analyze the relations between national regulations and international treaties in regulating foreign investment. Methods: The research method used is document analysis and a qualitative approach to national regulations and international agreements related to foreign investment. Data is obtained from literature studies and relevant official documents. Novelty: This article presents a novel contribution by summarizing and analyzing the legal framework involving foreign investment in the era of globalization, as well as highlighting the significant differences between national regulations and international treaties in the context of foreign investment protection. Results and Discussion: The analysis shows that there are complexities in the relationship between national regulations and international treaties in providing legal protection for foreign investment. National regulations tend to reflect domestic interests while international treaties emphasize harmonization and protection of investments globally. Conclusion: There needs to be effective coordination between national regulations and international agreements to provide optimal legal protection for foreign investment in the era of globalization. A balance between the two aspects is important to create a stable and favorable investment environment for all relevant parties.